Development of Learning Media for the Digital Native Generation - Freddy Antara; Ardipal (UM Purwokerto Press, 2024)
Digital Native is someone who was born in the 21st century, where the role of technology cannot be separated from his daily life, as well as in learning the art of music composition, the presence of the Score Creator application greatly assists the teacher's role both in conveying music material, analyzing music to creating a work of musical composition. Apart from that professional teachers are also required to develop an ideal learning model that is appropriate to the era, so that the classic problems that are often found by teachers in learning will be greatly assisted. This study aims to determine the benefits of Score Creator in learning music composition. This type of research is (research and development). The development steps chosen by the researcher refer to the ten steps of implementing the research and development strategy according to Borg and Gall. The results of the study show that by using the score creator music application learning music composition is more effective. The learning model developed can maximize students' abilities in making a piece of music. Students will find it easy to write notations, compose compositions and provide interpretations of the works they create, and be able to perform well-performed music without the need for expertise in playing musical instruments.